Non-uniform self-assembly: On the anisotropic architecture of α-synuclein supra-fibrillar aggregates - Semerdzhiev, Slav A. (Sci Rep, 2017)
Although the function of biopolymer hydrogels in nature depends on structural anisotropy at mesoscopic length scales, the self-assembly of such anisotropic structures in vitro is challenging. Here we show that fibrils of the protein α-synuclein spontaneously self-assemble into structurally anisotropic hydrogel particles. While the fibrils in the interior of these supra-fibrillar aggregates (SFAs) are randomly oriented, the fibrils in the periphery prefer to cross neighboring fibrils at high angles. This difference in organization coincides with a significant difference in polarity of the environment in the central and peripheral parts of the SFA. We rationalize the structural anisotropy of SFAs in the light of the observation that αS fibrils bind a substantial amount of counterions. We propose that, with the progress of protein polymerization into fibrils, this binding of counterions changes the ionic environment which triggers a change in fibril organization resulting in anisotropy in the architecture of hydrogel particles.